Low Fluence Ultraviolet-B Promotes Ultraviolet Resistance 8-Modulated Flowering in Arabidopsis - Zioutopoulou, Anna; Patitaki, Eirini; O’Donnell, Liz; Kaiserli, Eirini (Frontiers in Plant Science, 2022)
Ultraviolet-B (UV-B) irradiation (280-320 nm) is an integral part of sunlight and a pivotal environmental cue that triggers various plant responses, from photoprotection to photomorphogenesis and metabolic processes. UV-B is perceived by UVR8 (ULTRAVIOLET RESISTANCE 8), which orchestrates UV-B signal transduction and transcriptional control of UV-B-responsive genes. However, there is limited information on the molecular mechanism underlying the UV-B- and UVR8-dependent regulation of flowering time in plants. Here, we investigate the role of UV-B and UVR8 in photoperiodic flowering in Arabidopsis thaliana. Our findings suggest that UV-B controls photoperiodic flowering in an ecotype-specific manner and that UVR8 acts as a negative regulator of UV-B-induced flowering. Overall, our research shows that UV-B modulates flowering initiation through the action of UVR8 at the transcriptional level.